A BIBLIOMETRIC ANALYSIS OF TACTICAL LEADERSHIP: TRENDS, MODELS, AND FUTURE PERSPECTIVES (2000-2024) - Siahaan, Ungkap; Lesmonojati, Sigit; Isnianto, Zulfa; Kolbinus, Achmad; Rumekso, Ahli; Dewi, Ni Kadek Rafika; Indarto, Is; Achmad (Journal of Scientech Research and Development, 2024)
This paper presents a bibliometric analysis of tactical leadership research, using data from the Scopus database spanning 2000 to 2024. The study examines publication trends, identifies key thematic areas, and highlights influential works within the field. Results indicate a notable increase in scholarly attention over the past two decades, marked by shifts toward integrating technological advancements and adaptive strategies in leadership. Key themes include operational planning, decision-making models, and the adoption of AI and machine learning to enhance situational awareness. Despite these advances, the field remains fragmented, with many studies focusing on specific contexts without forming cohesive, cross-sectoral frameworks. Limitations in existing research, such as a narrow focus and underutilization of interdisciplinary approaches, are discussed, emphasizing the need for future studies to bridge these gaps. This paper contributes to the academic discourse by mapping the evolution of tactical leadership research, offering insights into past trends, current practices, and potential future developments. The findings underscore the importance of adaptive, inclusive, and technologically integrated leadership practices that align with modern operational demands.